Macroprudential policies and bank risk evidence from Vietnam - Hang Thu Do; Linh Hong Pham; Huyen Thanh Ta; Huong Thi Diem Nguyen (Cogent Economics & Finance)
This paper examines the impact of macroprudential policies (MPP) on reducing risks at commercial banks (CBs) in Vietnam. In the paper, the authors use secondary data collected from the financial reports of 29 CBs in Vietnam during 2009-2023 to form an unbalanced panel data set and apply the GMM model to evaluate the impact of macroprudential policies on risks at these CBs. The research findings indicate that these policies generally effectively reduce risks at CBs. Additionally, when multiple instruments are combined, they have a more substantial impact. Based on this, the authors provide several recommendations to enhance the effectiveness of macroprudential policies and mitigate risks at Vietnamese CBs.